PARADIGMA FISIKA QUR’ANI DALAM TRIDHARMA PERGURUAN TINGGI KEAGAMAAN ISLAM - Muslimah Susilayati; Mufiq Mufiq; Barid Syamsiyah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
This study aims to provide an overview on the application of the 'Qur'ani Physics' paradigm to the implementation of the Tridharma of Islamic Higher Education in Indonesia. Based on the qualitative-descriptive approach, the results of thisstudy suggest that the need for three stages to be carried out in the process of implementing the 'Qur'ani Physics' paradigm; First, the preparation phase, which begins with the equating of perceptions which the output is in the form of a decree on the integration team. Second, the planning phase, which consists of determining the main material, reviewing and revising the curriculum, as well as determining the strategic plan for research and community service. Third, the implementation phase, which consists of research and development, education and learning, as well as community service. With this integration model, the paradigm of the integration with its various philosophical variants is expected to become a solution for various social problems that occur in society. So that, organizing education at the Islamic Higher Education has a distinction with General Higher Education.